The impact of the adoption of data analytics on gathering audit evidence: a case of KPMG Zimbabwe - Wadesango, Newman; Muzvuwe, Fadzai; Stephen, Malatji (Journal of Management Information and Decision Sciences, 2022)
The aim of this research, on the KPMG Zimbabwe external audit and assurance department, is to understand the impact of adopting data analytics on gathering audit evidence. The study purposes to disclose how auditors perceive the utility of big data and data analytics to support auditing procedures and gathering audit evidence. The topic was triggered by the crescent awareness of accounts, audit firms, standard setters, and academics. The paper adopted a mixed methodology research. Data collected through questionnaires was analysed quantitatively using descriptive statistics specifically measures of central tendency (mode) and measures of frequency (percent) were used and an overall assessment through regression analysis was made. Data collected through interviews was analysed using qualitative coding and analysis. The research discovered that adoption of data analytics has a positive effect on gathering audit evidence and this was supported by other scholars who were reviewed in chapter two. Recommendation was given for KPMG to fully adopt data analytics as solutions to challenges faced when using data analytics were proffered.